Baseline Serum Uric Acid Levels Are Associated with All-Cause Mortality in Acute Coronary Syndrome Patients after Percutaneous Coronary Intervention - Ye, Ziliang; Lu, Haili; Long, Manyun; Li, Lang (Disease Markers, 2018)
Background. Whether serum uric acid (UA) is associated with all-cause mortality in patients with acute coronary syndrome (ACS) following percutaneous coronary intervention (PCI) remains unclear. Methods. We performed a retrospective cohort study of 2296 patients with ACS. Curve-fitting and Cox proportional-hazard regression models with a hazard ratio (HR) and 95% confidence interval (CI) were used. Results. During a mean follow-up of 246.31 ± 49.16 days, 168 (7.32%) patients died from all causes. Patients were divided into two groups [the high-UA group (n=566) and the low-UA group (n=1730)] based on the serum UA threshold value (5.6 mg/dl) identified through curve fitting. Fifty-three (9.36%) patients died in the high-UA group, and 115 (6.65%) patients died in the low-UA group. The difference between groups was statistically significant (P=0.031). Univariate analysis showed that the risk of all-cause mortality in the high-UA group was significantly greater than that in the low-UA group (HR = 1.45, 95% CI: 1.03 to 2.04). This difference persisted after adjustment for baseline characteristics, medical history, and medication history (HR = 1.42, 95% CI: 1.05 to 1.87). Conclusions. Our study demonstrated that elevated serum UA (>5.6 mg/dl) is associated with all-cause mortality in ASC patients after PCI.